(untitled) (Research, Society and Development, 2022)
Objectives: To compare the techniques Pompage and Crochet in seamstresses with lumbar pain. Methodology: Characterization as a clinical, approved, analytical, intentional prospective study, carried out in a textile industry in the city of Teresina Piauí with 12 participants. Results: The research showed that the groups, Crochetagem presented a good level of significance in the lumbar compared to Pompage. And both by the SF-6 groups, in the final assessment, 3 designed to improve quality of life. Conclusion: The study presented, in both groups, satisfactory and positive results in the pain in the lumbar region of the participants who have a professional occupation focused on sewing. Crochetagem, however, presented a better level of significance in relation to Pompage.